Dynamic Game-Based Computation Offloading and Resource Allocation in LEO-Multiaccess Edge Computing - Haoyu Wang (Hindawi-Wiley, 2021)
The offloading of computing tasks in edge computing has always been a research hotspot and difficulty in recent years. As an effective way to run various applications on mobile devices with limited resources, it has been extensively studied by scholars from all walks of life. However, the traditional ground-based network-based edge computing network architecture cannot meet the needs of edge users with limited geographic areas. Therefore, this paper proposes an LEO (low earth orbit) satellite-based multiaccess edge computing network architecture and establishes a differential game model for this architecture. To obtain the Nash equilibrium solution of the open loop and the Nash equilibrium solution of the feedback for the task offloading amount, the relationship between the user’s income and the QoE level under the optimal task offloading amount is finally analyzed and discussed.